2006
DOI: 10.1096/fj.05-4763fje
|View full text |Cite
|
Sign up to set email alerts
|

G‐CSF administration after myocardial infarction in mice attenuates late ischemic cardiomyopathy by enhanced arteriogenesis

Abstract: Granulocyte-colony stimulating factor (G-CSF) has been shown to improve cardiac function after myocardial infarction (MI) by bone marrow cell mobilization and by protecting cardiomyocytes from apoptotic cell death. However, its role in collateral artery growth (arteriogenesis) has not been elucidated. Here, we investigated the effect of G-CSF on arteriolar growth and cardiac function in a murine MI model. Mice were treated with G-CSF (100 microg/kg/day) directly after MI for 5 consecutive days. G-CSF applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
123
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 45 publications
6
123
2
2
Order By: Relevance
“…Animal studies have demonstrated a beneficial effect of G-CSF mobilization of stem cells on left ventricular function after myocardial infarction, and this mobilization contributes to regenerative repair of the myocardium by inducing myogenesis and vasculogenesis and by diminishing post-infarction remodeling [4][5][6] . A recent study in mice has indicated that further mechanisms by which G-CSF improves cardiac function after myocardial infarction are associated with inhibiting apoptosis of cardiomyocytes through the Jak2-STAT3 pathway 7) and with promoting arteriogenesis by increasing intercellular adhesion molecule-1 (ICAM-1) expression on endothelial cells 8) .…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have demonstrated a beneficial effect of G-CSF mobilization of stem cells on left ventricular function after myocardial infarction, and this mobilization contributes to regenerative repair of the myocardium by inducing myogenesis and vasculogenesis and by diminishing post-infarction remodeling [4][5][6] . A recent study in mice has indicated that further mechanisms by which G-CSF improves cardiac function after myocardial infarction are associated with inhibiting apoptosis of cardiomyocytes through the Jak2-STAT3 pathway 7) and with promoting arteriogenesis by increasing intercellular adhesion molecule-1 (ICAM-1) expression on endothelial cells 8) .…”
Section: Introductionmentioning
confidence: 99%
“…In the present cases, cardiac function and blood pressure increased after G-CSF therapy and we hypothesize that increased cardiac function (increased stroke volume) resulted in elevation of blood pressure. Recent studies have demonstrated that G-CSF prevents cardiac remodeling by protecting cardiomyocytes and endothelial cells from apoptotic cell death [3]. Coincidently, the three dogs showed more improvement in left ventricular wall motion than in interventricular wall motion after G-CSF therapy.…”
mentioning
confidence: 72%
“…Human medical research [3,4,7,15,17] has shown that granulocyte-colony stimulating factor (G-CSF) improves cardiac function after myocardial infarction (MI) through bone marrow cell mobilization and protection of cardiomyocytes from apoptotic cell death. Specifically, the importance of the number of mobilized stem cells for clinical effects was supported by the facts that a therapeutic effect was only seen in patients with increased circulating mobilized CD34+ stem cells [16].…”
mentioning
confidence: 99%
“…Several investigations have demonstrated the effect of these cytokines on cellular proliferation, differentiation, maturation, angiogenesis, and cardiac remodeling [68][69][70][71][72][73][74][75][76][77] . Interleukin-3 has demonstrated improvement in left ventricular function and survival in animal models with acute MI or ischemic cardiomyopathy, which might be explained by promotion of angiogenesis, inhibition of apoptosis or differentiation of cardiomyocytes 69,71,72,75 . Fractalkine has demonstrated a role in delaying the enlargement of ventricular chambers following myocardial infarction 77 .…”
Section: Proteomics Analysismentioning
confidence: 99%